The fasting and refeeding strategy, a viable alternative for optimising the consumption of balanced feed in the semi-intensive farming of white shrimp Litopenaeus vannamei - Castro Morán, Junior Jair (2021)
The aim of this study was to determine the effect of two or three days of fasting per week with an increase of 20% in the post-fasting ration on growth, survival, biomass, feed consumption and relative conversion factor (FCR) of Litopenaeus vannamei shrimp grown in the laboratory at a density equivalent to that of a semi-intensive system. The experiment was carried out in nine aquariums with 90 L of brackish water, each with eight shrimp weighing approximately 5.5 g (25 specimens/m2). The shrimp were fed twice a day, then the food residues, feces and exuviae were removed. The feed dosage was set according to a commercial table and adjusted according to the consumption of the previous day. Growth (average weight, weekly weight increase, percentage weight gain), survival, biomass, feed consumption and relative growth factor - FCR were evaluated for nine weeks. The shrimp fasting two days a week and increasing the post-fasting ration by 20% maintained a statistically similar weight and biomass to that of shrimp without fasting, achieving a saving of 27.4% in the feed supplied and a better FCR (1.18 vs. 1.52). Shrimp fasting three days a week had a significantly lower average weight and lower biomass, although their savings in feed consumption and their FCR were better than the other two treatments. Survival was 100% in all treatments. It is concluded that a two-day weekly fasting with a 20% increase in the post-fasting ration is feasible to optimize the use of balanced food in the culture of Litopenaeus vannamei at a density equivalent to that of a semi-intensive culture.